Radiological protection in the Spanish nuclear industry under Franco, 1939-1975 - Sanchez Vazquez, L. (2017)
In debates about nuclear controversy, the issue of occupational safety in radioactive facilities is rarely foregrounded; it has historically been relegated to second place compared to the attention given to potential harm to the general population. Aiming for, at least, partially filling this historiographical gap, this article deals with the development of occupational radiological protection in Spain under the dictatorship of General Franco (1939-1975). It covers the rise of radiological protection measures on an international level and the subsequent development of legislation in the case of Spain, a process that paralleled the growth of the nation s nuclear program. Finally, it explores the main evidence of the impact of ionizing radiation on Spain s working population.